Relationship Between Vitamin D Levels and Covid-19 Severity Due to Circulating SARS-COV-2 Variants in Argentina: A Presentation of Clinical Cases - Carmona, Maximiliano (2021)
There is growing evidence that serum vitamin D levels are inversely related to the severity of COVID-19. However, it is not yet known whether this relationship is observed independently of the type of variant of SARS-CoV-2 that has caused the infection or if this is variant-dependent. In this context, we studied a series of clinical cases with a positive diagnosis of COVID-19 and required hospitalization in the unit of critical care at a hospital from Argentina. At the time of this study, the variants of SARS-CoV-2 with the highest circulation in this country were the Lambda (Andina) and Gamma (Manaus) variants. The obtained results would indicate that the inverse relationship studied is evidenced, at least, against infection by the two variants mentioned. However, to deepen this possible relationship against other variants, additional studies should be carried out in populations with a different viral circulation profile.